2010
DOI: 10.1590/s1980-57642010dn40100007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and demographic characteristics of elderly patients with dementia assisted at an outpatient clinic in Southern Brazil

Abstract: The aging of the population is a worldwide phenomenon, where 60% of elders live in developing areas of the world such as Brazil, regions in which few studies have been carried out.ObjectivesThe goal of this study was to evaluate the clinical and demographic profile of patients with dementing disorders seen at a specialized outpatient clinic in South Brazil.MethodsA sample of 105 demented patients seen at the Dementia Outpatient Clinic from Hospital de Clínicas de Porto Alegre (HCPA), Brazil between June 2004 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1
1

Year Published

2013
2013
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
3
1
1
Order By: Relevance
“…Concerning the prevalence of different types of dementia, most part of Brazilian studies have found AD as the prevalent type of dementia, followed by VD [4][5][6]8,9,[19][20][21]24 , in contrast our study. Vascular Dementia is predominant over the sample, with 17.5%.…”
contrasting
confidence: 91%
See 2 more Smart Citations
“…Concerning the prevalence of different types of dementia, most part of Brazilian studies have found AD as the prevalent type of dementia, followed by VD [4][5][6]8,9,[19][20][21]24 , in contrast our study. Vascular Dementia is predominant over the sample, with 17.5%.…”
contrasting
confidence: 91%
“…Concerning to the mean age in the sample, the result showed a sample of younger people than that of several other studies that showed medians higher than 70 years old 5,19,[23][24][25] , despite of most of them were older than 60 years (67.5%). The study by Silva and Damasceno 9 , also in a tertiary care service showed similar results to ours.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Moscoso et al., 22 in thirty-one elderly patients with AD from the outpatient unit of CEREDIC (Clinics Hospital – Cognitive Reference Center), observed a mean Zarit score of 31.77 and NPI of 34.97, scores higher than those observed in our study. Godinho et al, 23 studying a sample of 64 clinical outpatients with Alzheimer's disease, observed a mean NPI score of 35. One possible explanation for this difference is that our sample was community-based, while Moscoso et al 22 evaluated a clinical sample.…”
Section: Discussionmentioning
confidence: 99%
“…Junta-se a tais desafios o aumento na incidência de doenças relacionadas ao envelhecimento (Aprahamian et al, 2009;Godinho, Gorczevski, & Heisler, 2010;Soares et al, 2012;World Health Organization [WHO], 2011). De fato, segundo a OMS (Organização Mundial da Saúde) (WHO, 2011), em todo o mundo ocorre um declínio na incidência de doenças infecto-contagiosas e, simultaneamente, aumenta a frequência de doenças crônicodegenerativas, processo este conhecido como transição epidemiológica.…”
Section: Lista De Tabelasunclassified